PERAN WANITA SEBAGAI IBU DALAM PENDIDIKAN ISLAM PERSPEKTIF MURTADHA MUTHAHHARI - Wira Sugiarto; Putri Sari Ayu; Siti Al Fiza (STAI Pelabuhan Ratu, 2023)
This research explores the thoughts of Murtadha Muthahhari (1919-1979) regarding the role of women, particularly as mothers, in providing Islamic education to children. Muthahhari, a thinker from Iran, is the central focus of this study. The aim of the research is to elaborate on Muthahhari's views regarding women's rights in accordance with their nature, with a specific focus on their role in educating children. The research methodology employed is literature review or library research. The primary data for this study are derived from the translated book by Murtadha Muthahhari titled